2017
DOI: 10.21831/cp.v36i1.11080
|View full text |Cite
|
Sign up to set email alerts
|

Peningkatan Self-Regulated Learning Skills Mahasiswa Pada Mata Kuliah Akuntansi Pengantar Melalui Problem-Based Learning

Abstract: Abstrak: Penelitian ini bertujuan untuk mengetahui: (i) peningkatan self-regulated learning skills (SRL) melalui implementasi problem-based learning (PBL) dan (ii) peningkatan kemampuan dosen pelaksana dalam mengimplementasikan PBL. Penelitian ini merupakan lesson study terbagi atas dua siklus dimana masing-masing siklus terdiri atas tahap plan, do, dan see.Subjek penelitian adalah mahasiswa Akuntansi Universitas Negeri Yogyakarta semester pertama yang mengambil mata kuliah Akuntansi Pengantar sebanyak 35 maha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 4 publications
0
10
0
3
Order By: Relevance
“…This project-based learning model is systematic involving students in (Sari et al, 2015;Suryandari et al, 2018). The project-based learning model is a learning method that uses problems as a first step in collecting and integrating new knowledge based on experiences in real activities (Diah & Riyanto, 2016;Istiningrum, 2017). So, it can be concluded that projectbased learning can make students active and provide opportunities for students to work independently in solving problems or projects that are obtained.…”
Section: Bt Tmentioning
confidence: 99%
See 1 more Smart Citation
“…This project-based learning model is systematic involving students in (Sari et al, 2015;Suryandari et al, 2018). The project-based learning model is a learning method that uses problems as a first step in collecting and integrating new knowledge based on experiences in real activities (Diah & Riyanto, 2016;Istiningrum, 2017). So, it can be concluded that projectbased learning can make students active and provide opportunities for students to work independently in solving problems or projects that are obtained.…”
Section: Bt Tmentioning
confidence: 99%
“…This systematic project-based learning model engages students in the formation of knowledge and skills through a long and structured search / inquiry process towards authentic, complex questions and assignment and product designs (Suryandari, Sajidan, Rahardjo, Prasetyo, & Fatimah, 2018). Project Based Learning is a learning method that uses problems as a first step in collecting and integrating new knowledge based on experiences in real activities (Diah & Riyanto, 2016;Istiningrum, 2017). It can be concluded that project-based learning is project work that contains complex tasks based on challenging questions and problems, and requires students to design, solve problems, make decisions, conduct investigations, and provide opportunities for students to work independently.…”
Section: Introductionmentioning
confidence: 99%
“…Besides, teachers keep continually develop active, innovative, and innovative learning methods at class. The research of Istiningrum (2017), for instance, found out that the learning methods such as problem-based learning is able to improve students' self-regulated learning skills. Moreover, the learning method of openended experiential learning cases is also proven improving students' professional judgment ability on making accounting decisions (Istiningrum, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Kemampuan berpikir kritis siswa terbentuk dan terasah dari proses kerjasama atau diskusi dengan teman kelompok untuk memecahkan masalah. Model Problem-Based Learning menggunakan permasalahan yang berkaitan dengan disiplin ilmu, penyidikan autentik, kolaborasi dan memamerkan hasil karya (Haryati, 2017;Istiningrum, 2017). Siswa diberi kesempatan untuk bereksperimen dan merefleksi terkait hasil keputusan yang telah dibuat.…”
Section: Pengujian Hipotesis Menggunakanunclassified